BUDAYA KHATAMAN AL-QUR?AN DI KALANGAN MUHAMMADIYAH - M. Yaser Arafat; Siti Mupida; Dwi Abu Taukhid (IAIN Manado, 2022)
Abstract; This article aims to describe the khataman Al-Qur?an among the Muhammadiyah community. Khataman Al-Qur?an is one of the various forms of Islamic culture at Indonesia which often held by Muslims who are attached to accomodative towards local culture, and non puritan. This study will examine the culture of khataman Al-Qur?an among the Muhammadiyah, an Islamic organization at Indonesia wich is know to be closely associated with puritanism. The data were abtained by observation, interview, and literature review. This study found that khataman Al-Qur?an among Muhammadiyah is a new culture. Khataman Al-Qur?an takes the form in the implementation of the Al-Qur?an recitation worship which only ?started? in the last two decades. Validity of this culture is still being debated in Muhammadiyah. Usually, the khataman Al-Qur?an is held in the authority of Muhammadiyah. Meanwhile, khataman Al-Qur?an among Muhammadiyah community is very quiet from the influence of local culture. However, Muhammadiyah actually made a new khataman Al-Quran culture that corresponds to the times, such as khataman in the context of birthdays.Keywords: Khataman Al-Qur?an, Muhammadiyah, New Culture.Abstrak; Artikel ini berbicara tentang budaya khataman Al-Qur?an di kalangan warga Muhammadiyah. Khataman Al-Qur?an merupakan satu di antara berbagai bentuk kebudayaan Islam di Indonesia. Hanya saja, khataman Al-Qur?an sering diadakan oleh kalangan umat Islam yang lekat dengan sikap akomodatif terhadap budaya lokal alias non-puritan. Penelitian ini akan mengkaji budaya khataman Al-Qur?an yang dilakukan oleh warga Muhammadiyah, sebuah organisasi Islam di Indonesia yang dikenal lekat dengan identitas puritanisme. Data dalam penelitian ini didapatkan dengan metode observasi, wawancara, dan tinjauan kepustakaan. Penelitian ini menemukan bahwa khataman Al-Qur?an di kalangan warga Muhammadiyah masih termasuk budaya baru. Di kalangan warga Muhammadiyah, khataman Al-Qur?an mengambil bentuk dalam pelaksanaan ibadah pembacaan Al-Qur?an yang baru ?dimulai? sekitar dua dekade terakhir. Biasanya khataman Al-Qur?an digelar dalam rangka Hari Ulang Tahun Muhammadiyah atau lembaga pendidikan yang berada di bawah otoritas Muhammadiyah. Sedangkan bentuk budaya khataman warga Muhammadiyah sangat sepi dari pengaruh budaya lokal.Kata kunci: Khataman Al-Qur?an, Muhammadiyah, Budaya Baru.?